Dinâmica Socioeconômica das Unidades de Conservação do Maranhão - Yata Anderson Gonzaga Masullo; Helen da Costa Gurgel; Anne Elizabeth Laques; Dionatan Silva Carvalho (Confins)
The present study aims to analyze the social and economic dynamics of the Conservation Units of the State of Maranhão, based on the development of the Social Development Index (IDS). With the purpose of evaluating in a synthetic way the social and economic dynamic of the PAs of the state aligned with the objectives of the protected area, as well as if the UC makes possible the improvement in the quality of life of the population. Based on multidisciplinary methodological parameters capable of correlating conditioning factors that influence the level of effectiveness of PAs, the proposed methodology was applied in 11 PAs of Maranhão. The research was divided into three stages: 1) Bibliographic review and collection of primary and secondary indicators; 2) Qualification and synthesis of variables based on the Analytic Hierarchy Process (AHP) and 3) Spatial analysis and regionalization of conservation units using the geostatistical method of Kriging. Thus, it was possible to identify that among the PAs under analysis, 27% had an unsatisfactory level, while 46% had an unsatisfactory degree, 18% had a medium level and 9% had a satisfactory level. In this scenario, it is identified that the non-effectiveness of these areas makes it impossible to optimize land use planning on a regional scale, in addition to generating income, employment and increasing quality of life.